2021
DOI: 10.3390/molecules27010122
|View full text |Cite
|
Sign up to set email alerts
|

Oenothein B in Eucalyptus Leaf Extract Suppresses Fructose Absorption in Caco-2 Cells

Abstract: Inhibition of fructose absorption may suppress adiposity and adiposity-related diseases caused by fructose ingestion. Eucalyptus leaf extract (ELE) inhibits intestinal fructose absorption (but not glucose absorption); however, its active compound has not yet been identified. Therefore, we evaluated the inhibitory activity of ELE obtained from Eucalyptus globulus using an intestinal fructose permeation assay with the human intestinal epithelial cell line Caco-2. The luminal sides of a cell monolayer model cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The number of available studies is limited to nine cases. Six of them used Caco-2 cells [30,32,[34][35][36][37]; two relied on Caco-2/TC7 cells [31,33], and only one was performed on an ex-vivo rat jejunum mounted in an Ussing chamber [38]. Most of these studies did not consider the simultaneous presence of more than one PP species (a common occurrence in a PP-rich diet) and the possible occurrence of competition/synergy among individual PP species [39].…”
Section: Effect Of Single Pp On Fru Uptake and Transport In Intestina...mentioning
confidence: 99%
See 3 more Smart Citations
“…The number of available studies is limited to nine cases. Six of them used Caco-2 cells [30,32,[34][35][36][37]; two relied on Caco-2/TC7 cells [31,33], and only one was performed on an ex-vivo rat jejunum mounted in an Ussing chamber [38]. Most of these studies did not consider the simultaneous presence of more than one PP species (a common occurrence in a PP-rich diet) and the possible occurrence of competition/synergy among individual PP species [39].…”
Section: Effect Of Single Pp On Fru Uptake and Transport In Intestina...mentioning
confidence: 99%
“…In addition, the methods and the duration of supplementation were not consistent. Some studies involved the pretreatment of intestinal cells with PP [32,33,35] in contrast with co-supplementation with FRU [30,31,34,36,37], whereas exposure times ranged from 5 min [37] to 24 h [35]. Despite these limitations, PP supplementation studies generally resulted in a concentration-dependent decrease in FRU uptake [32,[34][35][36][37] and transport [30,31,33,34,38].…”
Section: Effect Of Single Pp On Fru Uptake and Transport In Intestina...mentioning
confidence: 99%
See 2 more Smart Citations
“…Oenothein B (OEB) is a macrocyclic ellagitannin dimer produced by members of the plant kingdom. In 1990, OEB was first identified in the leaves of Oenothera erythrosepala ( 14 ), and it was subsequently found in plants from the families Onagraceae, Lythraceae, and Myrtaceae ( 15 17 ). Several previous studies have revealed that OEB possesses diverse biological properties including antioxidant, anti-inflammation, antitumor, immunomodulatory, and antimicrobial activities ( 18 23 ).…”
Section: Introductionmentioning
confidence: 99%